Implementasi Metode Experiential Learning dalam Pembelajaran Ilmu Pengetahuan Alam di MI At-Thohiriyah - Najmi, Nurul; Nurjannariah , Nurjannariah; Yulianti, Nurul (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study aims to analyze the implementation of the Experiential Learning method in Natural Science (Ilmu Pengetahuan Alam, IPA) learning at MI At-Thohiriyah. The research employs Classroom Action Research (CAR) using the Kemmis and McTaggart model, consisting of planning, action, observation, and reflection in two cycles. The subjects are fourth-grade students who struggle to grasp science concepts through conventional teaching methods. Data were collected through observations, interviews, learning outcome tests, and documentation. The findings indicate that applying the Experiential Learning method significantly enhances students’ conceptual understanding of science and engagement in learning. In the first cycle, student learning outcomes improved by 20%, while in the second cycle, they increased to 42%. This method enables students to learn through direct experiences, experiments, and exploration, making abstract science concepts easier to understand. This study concludes that Experiential Learning is an effective method for improving science learning outcomes at the Madrasah Ibtidaiyah level.